Islamic Education Teachers’ Perceptions of the Curriculum Change from the 2013 Curriculum to the Independent Curriculum - Muhammad Ma'ruf Asy'ari; Riza Arif M.Z; Indah Aminatuz Zuhriyah; Muh. Noaf Afgani (South Sulawesi Education Development (SSED), 2024)
Curriculum change is one of the problems that arises related to the curriculum. There were various responses from teachers, students and parents regarding this curriculum change. Some of them argued that the curriculum was changed too quickly, giving rise to statement